(3fHPI ef cJGH GdUdGIs - (3egOj Hf Ydj cGTa GdZWGAs ((3YHO GdMSjf cGTa GdZWGAs)
(3ChdgG (B:s
(3cJGH GdUdGI, bjd Ef GdUdGI dZI ef Gddg GdQMeI(B...s
(3BNQgG (B:s
(3SGOSgG Cf Jbhd(B... (3bO jchf GdeHjY fbOG Ohf GdKef hbO jchf cdGgeG fbOGs
(3efbhdI ef fSNI GdeDdas
(3JHUQI GdYfhGf (B:s
(3QSGdI aj GdUdGIs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis